AN ANALYSIS OF POLITENESS STRATEGIES USED BY THE MAIN CHARACTERS OF “THE CHRONICLES OF NARNIA: THE LION, THE WITCH, AND THE WARDROBE” MOVIE - Annisa, Nurul; Mahmud, Murni (Faculty of Languages and Literature, Universitas Negeri Makassar, 2023)
This research analyzed “The Chronicles of Narnia: The Lion, The Witch, and The Wardrobe” movie. The analysis of this research focuses on the use of Politeness Strategies by the main characters, namely Peter Pevensie, Edmund Pevensie, Susan Pevensie, Lucy Pevensie, Jadis, Mr. Tumnus, and Aslan in “The Chronicles of Narnia: The Lion, The Witch, and The Wardrobe” movie. This research aimed to determine the kind of politeness strategies used by the main characters, and to find the meaning of politeness in the film. This research used a descriptive qualitative method. The data of this research were obtained from the transcript of “The Chronicles of Narnia: The Lion, The Witch, and The Wardrobe” movie. The data analysis applied using interactive model analysis which includes data reduction, data display, and conclusion (Miles & Huberman, 2014). The results of this research indicated that there were 4 kinds of politeness strategies used by the main characters in the film, namely positive face/positive politeness, negative face/negative politeness, bald-onrecord, and off-record. In addition, this research also showed the meaning of politeness used by the main characters in the film. The meaning of politeness used by the main character is categorized into 2 types, namely denotative meaning and connotative meaning.